Etiopathogenetic, Morphological, Diagnostic and Therapeutic Aspects of Acute Glomerulonephritis: Current Status - I. T. Murkamilov; I. S. Sabirov; V. V. Fomin; Zh. A. Murkamilova; K. A. Aytbaev (Архивъ внутренней медицины)
The review provides up-to-date information on the etiological factors and pathogenic mechanisms of development, morphological changes, clinical and laboratory manifestations of acute glomerulonephritis, as well as therapeutic possibilities for its treatment. The review provides up-to-date information on the etiological factors and pathogenetic mechanisms of development, morphological changes, clinical and laboratory manifestations of acute glomerulonephritis, as well as therapeutic possibilities for its treatment. The epidemiological issues of acute post-streptococcal glomerulonephritis are presented, indicating the characteristics of the effects of nephritogenic strains of Streptococcal infection. The immunopathological reactions of the body in acute glomerulonephritis to the causative agent of the disease and its antigens with the development of an imbalance of subpopulations of T-lymphocytes, the nephritogenic potential of streptococcal proteins, a marker of active proliferation of mesangiocytes, C3 and C4 fractions of complement, and also the renin-angiotensin-aldosterone system are shown. The article emphasizes that the informational content of serological tests in acute glomerulonephritis increases while assessing the C3 and C4 fractions of serum complement. The pathological effects of angiotensin II and aldosterone on the renal tissue with the chronization of acute glomerulonephritis, the development of nephrotic proteinuria and a rapid decrease in renal function are presented. The data of a direct correlation between the severity of histological changes and the clinical manifestations of acute glomerulonephritis, possibly the prognosis, are shown. Presented are modern data on the assessment of the main clinical manifestations of acute glomerulonephritis (urinary syndrome, edema syndrome and arterial hypertension). When discussing the treatment of acute glomerulonephritis, the controversial issues of the use of antibiotic therapy, preventive tonsillectomy are noted. The literature data on the treatment options for edematous syndrome and arterial hypertension using thiazide and loop diuretics, calcium antagonists, beta-blockers, angiotensin converting enzyme inhibitors, angiotensin II receptor blockers are presented. The issues of immunosuppressive therapy using glucorticoids, as well as prognostic criteria for acute glomerulonephritis are discussed.